Traditional maize/legume intercropping: IPSR Innovation Profile - Thierfelder, Christian L. (2022)
Intercropping is traditionally practiced by land constrained smallholder farmers sometimes living in steep and/or uneven terrain. Intercropping is the practice of growing two or more crops in the same area, at the same time. In general, intercropping is better suited to farmers with small landholdings whereas crop rotation is more suitable for farmers with larger landholding. However, there are other factors such as household needs and farm economics that determine choice of these two practices. The land equivalent ratio (LER) is often used to measure benefits of intercropping compared to planting a single crop (sole cropping). The LER is defined as the land required for production of the same yield in the sole crops compared with the intercrop. A LER greater than 1 indicates intercropping is advantageous to sole crops.